1.-【-a^2]^3*[-a]^2/[-a^2] 2.[2x^2+3x+5]^2-[2x^2+3x+4]^2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 07:42:31
1.-【-a^2]^3*[-a]^2/[-a^2]2.[2x^2+3x+5]^2-[2x^2+3x+4]^21.-【-a^2]^3*[-a]^2/[-a^2]2.[2x^2+3x+5]^2-[2x^2
1.-【-a^2]^3*[-a]^2/[-a^2] 2.[2x^2+3x+5]^2-[2x^2+3x+4]^2
1.-【-a^2]^3*[-a]^2/[-a^2] 2.[2x^2+3x+5]^2-[2x^2+3x+4]^2
1.-【-a^2]^3*[-a]^2/[-a^2] 2.[2x^2+3x+5]^2-[2x^2+3x+4]^2
1、(A^6×A^2)/(-a^2)=-A^6
2、令2x^2+3x+4=T
则原式变为(T+1)²-T²=2T+1=4X^2+6x+5
计算(3a×a)+(2a×3a)+(3a×a)+[a×(a+2a+2a+2a+a)]
(a 1)(a 2)(a 3)(a
(a+2)(a+1)-a(a-3)
计算;(a^3)^4+a^10×a^2-a×a^2-a*a^3*a^8
a-2a+3a-4a+5a-6a+...+99a-100a
化简; a-2a+3a-4a+5a-6a+``````-2006a+2007a.
(a+3a+5a+...+2009a)-(2a+4a+6a+...+2008a)=
(a+3a+5a+.+2009a)-(2a+4a+6a+.2008a)
计算(a+3a+5a+...+2009a)-(2a+4a+6a+...+2010a)
(a+3a+5a+...+2013a)-(2a+4a+6a+...+2012a)=
化简:a-2a+3a-4a+5a-6a+.+2010a+2011a.
计算(a+3a+5a+.+2003a)-(2a+4a+6a+...+2004a)
(a+3a+5a+.+2003a)-(2a+4a+6a+.+2004a)
(a+3a+5a...+2009a)-(2a+4a+6a+...+2010a)=?
5a^-〔a^-2a-2(a^-3a)]
a(a-1)(a-2)(a-3)(a-4)因式分解
【1】a+a=a×a a= [ ]【2】a×a=a÷a a=[ ]【3】a×a=a-a a=[ ] [4]a-a=a+a a=[ ]
(通分) a/a^a^a+3a+2 ,a/a^a+2a+1 ,-1/3a+6